John Laird. - Sahl, Ted (photographer):::Creator::::::::::::
Fundraiser for John Laird's California Assemblyman race. From left-to-right are John Laird, unidentified male, Ken Yeager, and unidentified male. Laird won the seat and served in the Assembly from 2002 to 2008. Ken Yeager was a member of the San Jose City Council and later became a member of Santa Clara County Board of Supervisors.